Kinetic disruption of lipid rafts is a mechanosensor for phospholipase D - Petersen, E. Nicholas; Chung, Hae-Won; Nayebosadri, Arman; Hansen, Scott B. (Nature communications, 2016)
The sensing of physical force, mechanosensation, underlies two of five human senses—touch and hearing. How transduction of force in a membrane occurs remains unclear. We asked if a biological membrane could employ kinetic energy to transduce a signal absent tension. Here we show that lipid rafts are dynamic compartments that inactivate the signalling enzyme phospholipase D2 (PLD2) by sequestering the enzyme from its substrate. Mechanical disruption of the lipid rafts activates PLD2 by mixing the enzyme with its substrate to produce the signalling lipid phosphatidic acid (PA). We calculate a latency time of <650 μs for PLD activation by mixing. Our results establish a fast, non-tension mechanism for mechanotransduction where disruption of ordered lipids initiates a mechanosensitive signal for cell growth through mechanical mixing. Mechanosensation by biological membranes can be relayed by mechanical tension to ion channels. Here the authors show that phospholipase D (PLD) is activated by mechanical disruption of lipid rafts which allows PLD to mix with its substrate in the lipid membrane, and propose a kinetic model of force transduction.